2011
DOI: 10.1007/s12015-011-9255-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Neural Crest Stem Cells (hEPI-NCSC)—Characterization and Directed Differentiation into Osteocytes and Melanocytes

Abstract: Here we describe the isolation, characterisation and ex-vivo expansion of human epidermal neural crest stem cells (hEPI-NCSC) and we provide protocols for their directed differentiation into osteocytes and melanocytes. hEPI-NCSC are neural crest-derived multipotent stem cells that persist into adulthood in the bulge of hair follicles. Multipotency and self-renewal were determined by in vitro clonal analyses. hEPI-NCSC generate all major neural crest derivatives, including bone/cartilage cells, neurons, Schwann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 55 publications
11
112
0
2
Order By: Relevance
“…In recent years, Sox10 + stem cells have been reported to exist in multiple adult tissues, including inferior turbinate23, periodontal ligament24, hair follicle2526, mammary epithelium27, and bone marrow28. Sox10 could also promote tumor formation29.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Sox10 + stem cells have been reported to exist in multiple adult tissues, including inferior turbinate23, periodontal ligament24, hair follicle2526, mammary epithelium27, and bone marrow28. Sox10 could also promote tumor formation29.…”
Section: Discussionmentioning
confidence: 99%
“…rdzenia kręgowego. Naukowcom z Uniwersytetu w Newcastle udało się przekształcić komórki macierzyste skóry w osteocyty i melanocyty [13]. Od 2006 roku wykorzystywana jest metoda genetycznego przeprogramowania fibroblastów skóry in vitro tak, aby mogły cofnąć się do etapu niedojrzałego oraz niezróżnicowanego i były w stanie rozwijać się w różne linie komórkowe.…”
Section: Typy Komórek Macierzystych W Skórzeunclassified
“…The presence of NCSC was demonstrated not only in the embryo but also in the adult tissues [8][9][10], and our group investigated the presence of NCSC in the adult PDL tissue using two immortalized clonal PDL cell lines with multipotency [63]. One of these, cell line 1-11, had the capacity to differentiate into osteoblasts and adipocyte, whereas the other clone, cell line 1-17, could differentiate into osteoblasts, chondrocytes, adipocytes, and neural cell.…”
Section: Periodontal Ligament Stem Cellsmentioning
confidence: 99%
“…Recent reports have demonstrated that NCSC are present not only in the neural crest in the embryo but also in their target tissues in fetal and adult tissues; human epidermal NCSC are multipotent remnants in a postnatal location. For example, NCSC can be found in the bulge of hair follicles where they persist postnatally and into adulthood [8][9][10]. In addition, many reports have identified the presence of stem cells in NCSC-derived dental tissues such as dental follicle, apical papilla, pulp, exfoliated deciduous teeth, and PDL, and numerous in vitro and in vivo studies [16-22, 24-45, 49-69].…”
Section: Introductionmentioning
confidence: 99%